Perilaku Wirausaha: Budaya dan Efikasi Diri - Anggie, Adelia Sepita; V, Yuhendri L. (Politeknik Piksi Ganesha Indonesia, 2025)
The importance of understanding local cultural factors and individual psychological aspects in shaping entrepreneurial behavior within tradition-based MSMEs. The purpose of this research is to analyze the influence of Batak Toba Ethnic Culture and Self-Efficacy on the Entrepreneurial Behavior of ulos cloth entrepreneurs in Medan. A quantitative method with a causal approach was applied, with data collected through proportional questionnaires distributed to ulos entrepreneurs. The data were analyzed using multiple linear regression to test both partial and simultaneous effects. The results show that Batak Toba Ethnic Culture significantly contributes to the development of work ethic, integrity, and long-term achievement orientation. Meanwhile, Self-Efficacy encourages risk-taking, innovation, and adaptability in facing business challenges. Simultaneously, these two factors strengthen entrepreneurial behavior that is adaptive, creative, and competitive. Therefore, reinforcing cultural identity and enhancing self-efficacy are effective strategies for developing tradition-based MSMEs with strong competitiveness.